Highly stable and efficient planar perovskite solar cells using ternary metal oxide electron transport layers - Thambidurai, Mariyappan (2021)
In planar perovskite solar cells, the electron transport layer (ETL) plays a vital role in effective extraction and transportation of photogenerated electrons from the perovskite layer to the cathode. Ternary metal oxides exhibit excellent potentials as ETLs since their electrical and optical properties are attunable through simple compositional adjustments. In this paper, we demonstrate the use of solution-processed zinc oxide (ZnO) and zinc tin oxide (ZTO) films as highly efficient ETLs for perovskite solar cells. We observe poor compatibility between ZnO and perovskite which impedes device reproducibility, stability, and performance unlike ZTO ETL devices. Furthermore, we modify the ZTO/perovskite interface by introducing a thin passivating SnO2 interlayer. The Zn1Sn1Ox/SnO2 ETL device demonstrates paramount power conversion efficiency (PCE) of 19.01% with corresponding short circuit current density (Jsc), open circuit voltage (Voc), and fill factor (FF) values of 21.93 mA cm−2, 1.10 V, and 78.82%. Moreover, the Zn1Sn1Ox/SnO2 ETL device displays superior stability, maintaining 90% of its initial PCE after 90 days in the absence of encapsulation at relative humidity of 30–40%. Enhancement in charge extraction, favourable energy alignment, and reduction in recombination sites greatly contribute to the optimal performance, stability, and reproducibility of the Zn1Sn1Ox/SnO2 ETL device.